Fixed-bandwidth CUSUM tests under long memory - Christian Leschinski; Kai Wenger (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2018)
We propose a family of self-normalized CUSUM tests for structural change under long memory. The test statistics apply non-parametric kernel-based fixed-b and fixed-m long-run variance estimators and have well-defined limiting distributions that only depend on the long-memory parameter. A Monte Carlo simulation shows that these tests provide finite sample size control while outperforming competing procedures in terms of power.
Keywords: C12; C22; 330; Fixed-bandwidth asymptotics; Fractional Integration; Long Memory; Structural Breaks